The Influence of Influencer Marketing and Brand Image on the Purchase Decision of Local Make Up Brands in Cirebon City - Pasaribu, Lukas Natanael; Fauziah, Erika; Hernidatiatin, Listatin (International Journal of Business, Economics, and Social Development, 2025)
One of the global trends with the greatest rate of growth is the usage of beauty items, particularly makeup kits. The majority of women prefer to purchase cosmetics from local brands, per Databoks data. In Indonesia, up to 53% of women select native cosmetics, with the remaining 11% favoring foreign products. This demonstrates how well-liked local cosmetic brands are by women. This study concentrates primarily on local brands, particularly Wardah cosmetics made by PT Paragon Technology and Innovation, which has introduced a number of cosmetic goods, out of the numerous makeup brands that are available in the Indonesian beauty industry. Analyzing the impact of influencer marketing, brand perception, and consumer choices on the local beauty company Wardah in Cirebon was the aim of this study. 384 respondents were obtained by applying the Cochran formula because this study took a quantitative approach with an unknown population. Smart-PLS software version 4.0 was utilized for data analysis and structural equation modeling (SEM), while a Likert scale questionnaire was employed to collect primary data. The findings demonstrated that brand image (X2) and influencer marketing (X1) significantly and favorably influenced consumers' decisions to buy local makeup products in Cirebon City (Y).